Implementasi Ketentuan Zakat Mal terhadap Hasil Petani Rumput Laut di Kabupaten Pangkep: Analisis Mazhab Fikih - Ariska, Ariska; Arsyad, Azman; Ariyanti, Riska (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2024)
Zakat mal is a problem that is getting warmer and warmer day by day among the community, especially in the community of Pitue village, Ma'rang sub-district, Pangkep district, where we can see that from the distribution system and the zakat provisions do not have clear standards in the Shari'a because they don't really believe in BAZNAS or other institutions so as to trigger various perceptions in the implementation of zakat. This article aims to identify the basis and procedures for implementing seaweed mal zakat. This study discusses the seaweed mal zakat in Pitue village, Ma'rang sub-district, Pangkep district by using fiqh school of analysis. This research is field research with an ethnographic, sociological, and normative (Syari'i) approach. The data sources used in this study were survey methods and interviews with informants and also took from related books and journals, in addition to data collection methods and data analysis by means of observation, interviews and using atlas.ti9 software. In this study it was found that the provisions for zakat mal seaweed in Pitue village were where the farmers did not have standard provisions that they used as references. However, in a more in-depth study, there are a small number of them referring to the provisions of trade mall zakat at a rate of 10% annually.